Eveningness as a risk for behavioral problems in late adolescence. (7th February 2017) - Merikanto, Ilona; Pesonen, Anu-Katriina; Kuula, Liisa; Lahti, Jari; Heinonen, Kati; Kajantie, Eero; Räikkönen, Katri
ABSTRACT: Circadian preference toward eveningness has been associated with increased risk for mental health problems both in early adolescence and in adulthood. However, in late adolescence, when circadian rhythm naturally shifts to later, its significance for mental health is not clear. Accordingly, we studied how circadian rhythm estimated both by self-reported chronotype and by actigraph-defined midpoint of sleep was associated with self-reported psychiatric problems based on Youth Self Report (YSR). The study builds on a community cohort born in 1998, Helsinki, Finland. At age 17 years (mean age = 16.9, SD = 0.1 years), 183 adolescents (65.6% of the invited) participated in the study. We used the shortened version of the Horne-Östberg morningness–eveningness Questionnaire to define the chronotype, and actigraphs to define the naturally occur circadian rhythm over a 4 to 17 days' period (mean nights N = 8.3, SD = 1.8). The Achenbach software was used to obtain T-score values for YSR psychiatric problem scales. The analyses were adjusted for important covariates including gender, socioeconomic status, body mass index, pubertal maturation, mother's licorice consumption during pregnancy, and actigraph-defined sleep duration and quality. Eveningness was associated with higher scores in rule-breaking behavior and conduct problems (as assessed either by midpoint of sleep or by self-reported chronotype, p -values <0.05), attention deficit/hyperactivity problems (by self-reported chronotype, p -values <0.05), with affective problems (by midpoint of sleep and by self-reported chronotype, p -values <0.05) and somatic complaints (by self-reported chronotype, p -values <0.05), as compared to circadian tendency toward morningness. Our results suggest that the association between eveningness and externalizing problem behavior, present in children and younger adolescents, is also present in late adolescence when circadian rhythms shift toward evening.